Psychological Impact of Sexual Violence and Government Efforts in Making Recovery (Journal of Creativity Student, 2021)
This article aims to describe the psychological impact of sexual violence and the government's efforts to restore victims. The discussion of this article uses a written study from various reading sources which is entirely aimed at developing speculations related to the growth of victims, the causes of sexual brutality in children and the impact and treatment of sexual crimes on children, as well as on adults. Sexual violence is an activity that is carried out by someone without the consent or willingness of the person who is the victim of the sexual violence. In this sexual violence the acts are in the form of rape by a stranger, rape in a marriage relationship and there is also courtship, this sexual harassment can be in the form of mental or physical abuse, forced abortion, and there is also sexual abuse of children. Of the types of sexual violence is a form of violation of human rights (HAM) that can have a psychological impact on victims of sexual violence. "Theresia" in the Pulih Foundation Webinar with The Body Shop Indonesia, Tuesday (29 June 2021) said that the psychological impact on victims of sexual violence for example, such as mental disorders, depression, personality disorders, psychotic disorders, panic disorders, trauma, insomnia, and symptoms of disorders that cause unable to be himself, then there are thoughts of ending his life, abusing drugs and alcohol for him to escape from the problems he faces and to make his life more calm”. In these cases of sexual violence, the government provides efforts for psychological recovery to victims of sexual violence. Preventive efforts and repressive efforts. The research objectives of this article are to find out how sexual violence occurs, the psychological impact of sexual violence, and to find out how the psychological dynamics of victims of sexual violence are. And the results of this study indicate that the psychological impact of subjects who are victims of sexual violence is the presence of post-traumatic stress disorder. In addition to having a psychological impact, the psychological dynamics of the subjects in this study also have similarities, but there are some striking differences. The magnitude of the difference in psychological impact and dynamics is caused by several factors such as personality characteristics, ways of solving problems.